Interaction of Chlamydia psittaci with mouse peritoneal macrophages. - Wyrick, P B (1978)
L-cell-grown Chlamydia psittaci elementary bodies (EB) were rapidly phagocytized by mouse peritoneal macrophages in vitro. However, the intracellular fate of chlamydiae in macrophages appeared to be dependent on the multiplicity of infection (MOI), i.e., the EB-to-macrophage ratio, and the treatment of the EB. At an MOI of 1:1 or less, survival is maximal, and growth and multiplication of live, untreated chlamydiae did occur. In contrast, at a high MOI (100:1), survival of chlamydiae is reduced, as confirmed by release of 3H-labeled nucleic acid into the supernatant. At the high MOI, macrophage damage occurred that resulted in significant release of the lactic dehydrogenase, beginning 2 h postinfection. This immediated macrophage cytotoxicity as abolished by pretreatment of EB with heat (5 min at 56 degrees C) and was reduced about 50% by coating EB with homologous antibody. Pretreatment of the chlamydia with heat or opsonizing antibody provides increased uptake of EB by macrophages but may contribute to increased destruction of these obligate intracellular pathogens in professional phagocytic cells.